2019
DOI: 10.1371/journal.pone.0225585
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported adverse drug effects and associated factors among H. pylori infected patients on standard triple therapy: Prospective follow up study

Abstract: BackgroundOne of the most common reasons for poor medication adherence and associated treatment failure of triple therapy is adverse drug effect (ADEs) of medications.ObjectiveAssessment of ADEs and associated factors during H. pylori eradication therapy.MethodConsented H. pylori positive adult outpatients on standard triple therapy (proton pump inhibitor, amoxicillin and clarithromycin) were involved in this facility based follow up study from May 2016 to April 2018 at Bahir Dar city in Ethiopia. Pre-develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Unfortunately, our patient suffered from ADRs and the therapy had to be stopped after 7 days. Eradication therapy ADRs are relatively common and expected [ 23 ], so a second eradication attempt was planned 2 months later after penicillin allergy and H. pylori antibiotic sensitivity testing to plan the optimal treatment strategy [ 24 ]. Unfortunately, bloody diarrhea developed on the 5th day, and colonoscopy revealed pancolitis that was initially considered either antibiotic-associated or hemorrhagic.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our patient suffered from ADRs and the therapy had to be stopped after 7 days. Eradication therapy ADRs are relatively common and expected [ 23 ], so a second eradication attempt was planned 2 months later after penicillin allergy and H. pylori antibiotic sensitivity testing to plan the optimal treatment strategy [ 24 ]. Unfortunately, bloody diarrhea developed on the 5th day, and colonoscopy revealed pancolitis that was initially considered either antibiotic-associated or hemorrhagic.…”
Section: Discussionmentioning
confidence: 99%
“…This practice has been described to have more clinical importance in developing countries where testing of H. pylori after eradication therapy is infeasible due to several reasons mainly patients economic status. Although this study was part of our previous studies done to assess eradication rate and self-reported adverse drug effects, it was completely different in its objective, method and data analysis, following which the findings and associated implications were different [27,28].…”
Section: Introductionmentioning
confidence: 98%
“…Diarrhea, constipation, nausea, vomiting, epigastric pain, flatulence, metallic taste, and pain in the abdomen, especially in the epigastric region, are frequently occurring adverse drug reactions (ADRs) following SST therapy to combat H. pylori infection [86,87]. Another study revealed that over 26% of the research participants had experienced ADRs [88]. Among them, 85% had gastrointestinal issues, such as gastrointestinal distress, nausea, uncomfortable or infrequent bowel movements (typically less than three times per week), loose motions, stomach upset, an eating disorder frequently accompanied by unrestrained body weight loss, and headache [88,89].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that over 26% of the research participants had experienced ADRs [88]. Among them, 85% had gastrointestinal issues, such as gastrointestinal distress, nausea, uncomfortable or infrequent bowel movements (typically less than three times per week), loose motions, stomach upset, an eating disorder frequently accompanied by unrestrained body weight loss, and headache [88,89]. Another study revealed that over 45% of participants encountered principally gastrointestinal ADRs [90].…”
Section: Introductionmentioning
confidence: 99%